Clinical and laboratory features of childhood-onset primary Sjögren's syndrome: A retrospective study from China - Chenxi Liu; Yingying Jin; Hua Huang; Fei Ding; Xuemei Xu; Shengfang Bao; Zhen Yang; Yanliang Jin (Frontiers Media S.A., 2023)
IntroductionThe initial presentations of childhood-onset primary Sjögren's syndrome (C-pSS) vary, making diagnosis challenging. We aimed to improve the diagnosis and evaluation of C-pSS by summarizing its clinical and laboratory features.MethodsA total of 49 patients with C-pSS between July 2015 and August 2022 in the Department of Rheumatology and Immunology of Shanghai Children's Medical Centre were enrolled in this study. Their clinical manifestations and laboratory examinations of these patients were compared based on the presence or absence of thrombocytopenia and parotitis and whether the immunological markers, including anti-nuclear antibodies (ANA), rheumatoid factor (RF), anti-Ro52/SSA antibodies (anti-SSA/Ro52), anti-Ro60/SSA antibodies (anti-SSA/Ro60), and anti-Ro/SSB antibodies (anti-SSB), were positive.ResultsThe mean age at C-pSS diagnosis was 10.34 ± 3.45 years, and the ratio of boys to girls was 1:6. In the thrombocytopenia group, parotitis (P = 0.044), organ involvement except for hematology (P = 0.002), positive anti-SSB (P = 0.004), and positive RF (P = 0.001) were less frequently observed. Complement C4 (P = 0.038) and white blood cells (P = 0.002) levels decreased and increased significantly, respectively. Anti-SSB (P = 0.010) and RF (P = 0.004) positivity were independent potential protective factors against thrombocytopenia in patients with C-pSS. In the parotitis group, higher ANA titers (P = 0.027), higher focus scores on labial gland biopsy (P = 0.024), and positive RF (P = 0.001), anti-SSA/Ro60 (P = 0.003), and anti-SSB (P = 0.001) were observed more frequently. Furthermore, positive anti-SSB (P = 0.012) and positive RF (P = 0.028) were independent risk factors for parotitis in patients with C-pSS. The hemoglobin level was significantly lower in patients with positive anti-SSA/Ro52 and positive anti-SSA/Ro60 results (P = 0.022 and P = 0.029, respectively), while immunoglobulin G level was significantly higher in patients in the same group (P = 0.048 and P = 0.007, respectively).ConclusionsPositive anti-SSB and positive RF values may be independent potential protective factors of thrombocytopenia in patients with C-pSS. In contrast, positive anti-SSB and positive RF were independent risk factors of parotitis in patients with C-pSS. More studies are needed to reveal the diagnostic role and pathogenic mechanism of immunological markers in C-pSS.